An Herbivore’s Thermal Tolerance is Higher Than That of the Ant Defenders in a Desert Protection Mutualism - Ginny Fitzpatrick; Goggy Davidowitz; Judith L Bronstein (Sociobiology)
In North American deserts, many species of cactus attract ants to their extrafloral nectaries; the ants actively defend the food source, and hence the plant, against herbivores. In thermally extreme environments, however, networks of positive and negative interactions like these are likely to be sensitive to the thermal limitations of each of the interacting species. We compared the thermal tolerance of a common phytophagous cactus bug, Narnia pallidicornis (Hemiptera: Coreidae), to that of the ants that defend the cactus Ferocactus wislizeni in the Sonoran Desert, USA. We used flow-through respirometry to experimentally determine the thermal limit of the herbivore and compared this to the thermal limits of the ant defenders, determined previously. In the field, we recorded herbivore frequency (proportion of plants with N. pallidicornis) and abundance (the number of N. pallidicornis per plant) in relation to ambient temperature, ant species presence and identity, and fruit production. We show that N. pallidicornis has a higher thermal tolerance than the four most common ant mutualists, and in the laboratory can survive very high temperatures, up to 43°C. Herbivore frequency and abundance in the field were not related to the daily high temperatures observed. Plants that were not defended by ants were occupied by more N. pallidicornis, although they showed no reduction in fruit set. Therefore, herbivory is likely to continue on fishhook barrel cacti even at high temperatures, especially those temperatures beyond the thermal tolerance of the ant defenders. The consequences of increased herbivory, however, remain unclear. Mutualisms are essential for ecosystem functioning; it is important to understand the thermal sensitivity of these interactions, especially in light of expected increases in global temperature regimes.